Back to the future: team-centred, resourcebased learning as the antecedent of computer-based learning - Cresswell , James E. (Research in Learning Technology, 1970)
With respect to staff efficiency, it is hard to beat the traditional lecture as a format for a university course. With a folder of lecture notes, multiple-choice assessment and an optical mark reader, it is equally easy for the academic to process 10 or 100 or 500 students. Indeed, the example of many American universities suggests that class size need be limited only by the capacity of the auditorium.DOI:10.1080/0968776980060110